Factors Contributing to Delay in Diagnosis and Start of Treatment of Leprosy: Analysis of Help-seeking Narratives from a Community Study in Dang District - Subedi, Madhusudan; Engelbrektsson, Ulla-Britt (Dhaulagiri Journal of Sociology and Anthropology, 2018)
Prolonged delays between first symptoms and diagnosis easily result in more impairment in newly detected leprosy patients, and aggregate negative consequences for individuals and their families. In cases of infectious leprosy, longer delays increase the risk for the spread of the disease. Limited studies have been carried out to explore the causes for delays in Nepal. This is a community level qualitative study conducted in Dang district. The information was obtained through in-depth interviews with 8 leprosy affected persons, 8 contacts, 8 community members and 5 service providers in Dang district. Skin patches were regarded as a simple skin disease, in particular of paucibacillary patients who had a limited number of skin lesions and no nerve damage. A local medical shop was the first choice for medicine to treat skin conditions. Delays in diagnosis of leprosy occurred at many stages from the development of the symptoms to consultation of health care services. The use of traditional medicine, a belief in self-cure and visit to traditional healers, and misdiagnosis (a disease other than leprosy by the health worker) and inadequate knowledge about the disease and its early symptoms were the main factors that influenced the delayed diagnosis. Delays accumulated as the result of series of help-seeking actions that reflected local socio-cultural beliefs and practices. Misdiagnoses could be reduced if adequate information on leprosy is given to community people and health service providers. Specific interventions are needed to promote knowledge and a good attitude among contacts and community members. To reduce patient delay, public health promotion is needed to increase the awareness of leprosy, and the health service delay should be reduced by improving diagnostic skills in public and private sectors. Addressing both components of delays will decrease the time to diagnosis and ultimately the extent of transmission of the disease and reduce the risk of nerve function impairments.